Bilateral inferior petrosal sinus sampling. (27th April 2011) - Deipolyi, Amy R; Hirsch, Joshua A; Oklu, Rahmi
Abstract : Bilateral inferior petrosal sinus sampling, the gold standard assay in diagnosing pituitary secretion of adrenocorticotropic hormone in Cushing disease, is highly accurate and safe when performed by experienced interventionalists. We review the anatomic and technical considerations essential for safe and reliable practice.